Implementasi Metode Collaborative Learning Dalam Pembelajaran Statistika Untuk Meningkatkan Keterampilan 4C (Critical And Problem Solving Skills, Collaboration Skills, Communication Skills, And Creativity And Innovation Skills) Pada Siswa Kelas XI - Fitriyanti Fitriyanti; Intan Sukma Laras; Khuswatun Khasanah; Ilma Dea Anita; Fadilah Rahmawati (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: The purpose of this research is to improve critical and problem solving skills, collaboration skills, communication skills, and creativity and innovation skills (4C) in grade XI students in Statistical Learning with the Implementation of Collaborative Learning Methods. The research method used is experimentation, which is divided into two classes namely experimental class and control class. The sample technique we used was probability sampling, the samples taken in this study came from an affordable population of smk N 1 Wanayasa students in grade XI TKJ A and XI TKJ B in the 2020/2021 school year, with each student from the experimental class and control class of 24 students. Thus, the number of samples used was 48 students. Data collection techniques are carried out by giving pretes and postest questions for Statistics material in improving 4C capability using Collaborative Learning learning models. Test the research hypothesis using t-test and obtained the results of t > t table. Therefore, it can be concluded that there is a role of Collaborative Learning learning methods on Statistics material in improving 4C skills. Collaborative Learning methods can be an alternative for teachers in carrying out learning to create an active, effective and not boring learning atmosphere. Abstrak: Tujuan penelitian ini untuk meningkatkan keterampilan critical and problem solving skills,  collaboration skills, communication skills, and  creativity and innovation skills (4C) pada Siswa kelas XI dalam Pembelajaran Statistika dengan implementasi metode Collaborative Learning. Metode penelitian yang digunakan adalah eksperimen, yang dibagi menjadi dua kelas yaitu kelas eksperimen dan kelas kontrol. Teknik sampel yang kami gunakan adalah probability sampling, sampel diambil dalam penelitian ini berasal dari populasi terjangkau siswa SMK N 1 Wanayasa kelas XI TKJ A dan XI TKJ Bahun ajaran 2020/2021, dengan masing –masing siswa dari kelas eksperimen dan kelas kontrol 24 siswa. Sehingga, jumlah sampel yang digunakan yaitu 48 siswa. Teknik pengumpulan data dilakukan dengan pemberian soal pretes dan postest untuk materi Statistika dalam meningkatkan kemampuan 4C menggunakan model pembelajaran Collaborative Learning. Uji hipotesis penelitian menggunakan uji–t dan diperoleh hasil t hitung > t tabel. Sehingga dapat disimpulkan, bahwa terdapat peranan metode pembelajaran Collaborative Learning terhadap materi Statistika dalam meningkatkan kemampuan 4C. Metode pembelajaran Collaborative Learning dapat dijadikan alternatif bagi guru dalam melaksanakan pembelajaran untuk menciptakan suasana belajar yang aktif, efektif dan tidak membosankan.